IPN-PUA: An ultra-low density self-lubricating composite with IPN structure–liquid lubricant coupling mechanism - Weihua Cao; Xiao Yang; Haiwang Wang; Yu Dong; Changxin Liu; Bingli Fan; Xiaowen Qi (Friction)
The goal of net zero carbon emissions is of a great concern to energy conservation and emission reduction. In aerospace and other industrial fields, one of main energy consumption forms is friction between motion pairs, although the energy consumption caused by equipment mass cannot be ignored. Therefore, ultra-low density self-lubricating composites with an interpenetrating polymer network (IPN) structure–liquid lubricant coupling mechanism are designed and prepared in this work to meet the pressing requirements of energy saving and emission reduction. The liquid lubricant is locked in situ into polyurethane acrylate (PUA) with IPN structures (IPN-PUA structures). The thermodynamic, mechanical, and tribological properties, as well as the comprehensive density‒friction properties of the material with IPN-PUA structures were studied. After the liquid lubricant is locked into the IPN-PUA structure, the material possesses not only excellent self-lubricating properties but also good micro-mechanical properties, with a coefficient of friction (COF) of 0.0938, wear rate of 6.58×10−15 m3/(N·m) and nanoindentation modulus of 4.5 GPa. Compared with other polymeric materials, such composite materials also possess an ultra-low density of 1.107 g/cm3, which contributes to their excellent versatile self-lubrication and low-density characteristics.